ALDH1A3–Linc00284 Axis Mediates the Invasion of Colorectal Cancer by Targeting TGFβ Signaling via Sponging miR-361-5p - Chunlin Ke; Minmin Shen; Peirong Wang; Zhihua Chen; Suyong Lin; Feng Dong (International Journal of Genomics)
ALDH1A3 and Linc00284 involve in colorectal cancer (CRC) development; however, the regulatory mechanism is still unclear. In this study, we collected clinicopathological characteristics and tissue samples from 73 CRC patients to analyze the expression of ALDH1A3, Linc00284, TGFβ signaling and miR-361-5p using qPCR, Western blotting, and ELISA. Multiple CRC cell lines were evaluated in this study, and the highest level of ALDH1A3 was observed in SW480 cells. To investigate the regulatory mechanism, RIP and luciferase assays were used to validate the interaction between Linc00284, miR-361-5p, and TGFβ. Proliferation, viability, migration, and invasion assays were performed to profile the effects of the ALDH1A3–Linc00284 axis in CRC cell functions, which was upregulated in CRC tissues. Knockdown ALDH1A3 or Linc00284 significantly reduced TGFβ expression and suppressed the EMT process, while overexpression had opposite effects. miR-361-5p targeted TGFβ directly, which negatively correlated with ALDH1A3–Linc00284 expression and CRC progression. Mechanistically, upregulation of ALDH1A3–Linc00284 promotes colorectal cancer invasion and migration by regulating miR-361-5p/TGFβ signaling pathway. Dysregulation of the ALDH1A3–Linc00284-miR-361-5p-TGFβ axis causes CRC invasion, which might provide a new insight into the treatment of CRC.